GREEN AND SMART TECHNOLOGIES FOR SMART CITIES - Tomar, Pradeep, 1976-; Kaur, Gurjit, 1980- ([S.l.] : CRC PRESS, 2019)
The book starts with an overview of the role of cities in climate change and environmental pollution worldwide, followed by the concept description of smart cities and their expected features, focusing on green technology innovation. This book explores the energy management strategies required to minimize the need for huge investments in high-capacity transmission lines from distant power plants. A new range of renewable energy technologies modified for installation in cities like small wind turbines, micro-CHP and heat pumps are described. The overall objective of this book is to explore all the green and smart technologies for designing green smart cities.
OCLC-licensed vendor bibliographic record.
Keywords: Smart cities; City planning -- Environmental aspects; MATHEMATICS / General; NATURE / Environmental Conservation & Protection; TECHNOLOGY / Environmental Engineering & Technology